Next‐Generation Sequencing to Characterize Mitochondrial Genomic DNA Heteroplasmy. Issue 5 (9th May 2022) - Yang, Zeyu; Slone, Jesse; Huang, Taosheng
Abstract: Mitochondria play a very important role in many crucial cellular functions. Each eukaryotic cell contains hundreds of mitochondria with hundreds of mitochondrial genomes. Mutant and wild‐type mitochondrial DNA (mtDNA) may co‐exist as heteroplasmy and cause human disease. The purpose of the protocols in this article is to simultaneously determine the mtDNA sequence and quantify the heteroplasmy level using parallel sequencing. The protocols include mitochondrial genomic DNA PCR amplification of two full‐length products using two distinct sets of PCR primers. The PCR products are mixed at an equimolar ratio, and the samples are then barcoded and sequenced with high‐throughput next‐generation sequencing technology. This technology is highly sensitive, specific, and accurate in determining mtDNA mutations and the degree/level of heteroplasmy. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : PCR amplification of mitochondrial DNA Basic Protocol 2 : Analysis of next‐generation sequencing of mitochondrial DNA Basic Protocol 3 : Mutect2 pipeline for automated sample processing and large‐scale data analysis